Mediating Effects of Parental Expectations on Parental Participation in Early Literacy: A Dyadic Analysis - Solichah, Novia; Fardana, Nur Ainy (Psympathic : Jurnal Ilmiah Psikologi, 2025)
Parental participation is crucial in developing early literacy skills in children, but publication on the combined contributions of both fathers and mothers remains limited. Therefore, this study aims to investigate how parental motivational beliefs, subjective norms, and perceived life context influence participation in early literacy activities, with parental expectations serving as a mediating factor. Anchored in Theory of Planned Behavior (TPB), the analysis adopted dyadic method through Actor-Partner Interdependence Mediation Model (APIMeM), which examined both individual and partner effects. A time-lagged design was conducted with 507 father-mother dyads (N = 1014) across 10 kindergartens in Surabaya, Indonesia. The instruments used were carefully adapted to ensure cultural relevance and validity. The results showed that motivational beliefs, social norms, and perceived life context significantly predicted parental participation, with expectations mediating these relationships. This study underscored the importance of considering both parental psychosocial factors to strengthen early literacy support at home and guide the design of family-focused interventions.